Misrecognition - Newbound, Madison (Simon & Schuster, 2024)
"Elsa is struggling. Her formative, exhilarating relationship -- with a couple -- has abruptly ended, leaving her depressed and directionless in her childhood bedroom. The man and the woman were her bosses, lovers, and cultural guideposts. In the relationship's wake, Elsa scrolls aimlessly through the internet in search of meaning. Faithfully, her screen provides a new obsession: a charismatic young actor whose latest feature is a gay love story that illuminates Elsa's crisis. And then, as if she had conjured him, Elsa sees the actor in the flesh; he and an entourage of actors, writers, and directors have descended upon her hometown for the annual theater festival. When she is hired as a hostess at the one upscale restaurant in town, Elsa finds herself in frequent contact with the actor and his collaborators. But her obsession shifts from the actor to his frequent dinner companion -- an alluring, androgynous person called Sam. As this confusing connection develops, Elsa is forced to grapple with her sexuality, the uncomfortable truths about the dramatic end of her last relationship, and the patterns that may be playing out once again." -- Jacket flap